Multimarket Linkages, Cartel Discipline and Trade Costs - Delina Agnosteva; Constantinos Syropoulos; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2017)
We build a model of tacit collusion between firms that operate in multiple markets to study the effects of trade costs. A key feature of the model is that cartel discipline is endogenous. Thus, markets that appear segmented are strategically linked via the incentive compatibility constraint. Importantly, trade costs affect cartel shipments and welfare not only directly but also indirectly through discipline. Using extensive data on international cartels, we find that trade costs exert a negative and significant effect on cartel discipline. In turn, cartel discipline has a negative and significant impact on trade flows, in line with the model.
Keywords: D43; F10; F12; F13; F15; F42; L12; L13; L41; 330; endogenous cartel discipline; competitiveness; multimarket contact; welfare; trade flows; trade costs; trade policy; gravity